Desfechos clínicos e radiográficos de materiais obturadores de dentes decíduos com necrose pulpar : uma revisão sistemática - Alves, Nilton de Moura (2020)
Dental caries in primary teeth can lead to pulp necrosis and periodontal inflammation, which can affect children's quality of life. Pulpectomies are treatments used for cleaning, disinfection and filling of root canals with necrotic tissue. In order to maintain healthy and functional teeth, root canal filling materials are used in deciduous teeth pulpectomies for their antimicrobial properties and the ability to maintain tissues without clinical and radiographic aspects of infection and inflammation. The aim of this study was to conduct a systematic review of randomized clinical trials of root canal filling materials of deciduous teeth, to determine if any substance stands out for clinical and radiographic outcomes. Studies were searched in four databases (PUBMED, COCHRANE LIBRARY, SCIELO and EMBASE), using terms related to pulpectomy, root canal filling materials and deciduous teeth, resulting in an analysis of 845 scientific articles. After inclusion and exclusion criteria, 21 studies were selected for a qualitative analysis. The overall best clinical and radiographic success outcomes were found in the groups that used zinc oxide and iodoform fillers, with good performance over 6 to 24 months of follow-up.